Education Reform From An International Perspective - Levin, Benjamin (Education Policy Analysis Archives, 2001)
A great deal of comparative work on education reform is now being done, but this work often lacks a clearly articulated conceptual frame. This paper, based on a study of change in five jurisdictions in four countries, develops a model of reform based on four interactive elements - origins, adoption, implementation, and outcomes. Within each of these elements, questions and concepts from the relevant literature are developed with the intent of building a more comprehensive approach to the analysis of reform from political, organizational and educational perspectives.